ANALISIS MOTIVASI BELAJAR SISWA SD SELAMA PEMBELAJARAN DARING DI DESA KUDUKERAS KECAMATAN JUWANA KABUPATEN PATI - Rohmah, Fina Fatihatur; Ismaya, Erik Aditia; Masfuah, Siti (Universitas Muria Kudus, 2024)
The objectives of the study 1) Explain factors influence the motivation of elementary school children during online learning and 2) explain strategies are given by parents to motivate elementary school children to learn during online learning in Kudukeras Village, Juwana District, Pati Regency. The method used is descriptive qualitative. Data collection techniques using observation, interviews and documentation. The data analysis technique is by reducing the data, presenting the data, and concluding the data. The results of this study are 1) There are 3 (three) factors that influence the motivation of elementary school children during online learning in Kudukeras Village, Juwana District, Pati Regency. First, it is a matter of learning interest, so what is the purpose of learning and who is it for. Second, infrastructure includes the availability of devices and internet connections. Third, students include motivation, boredom, independence, and socialization. 2) The strategies given by parents for elementary school children's learning motivation during online learning in Kudukeras Village, Juwana District, Pati Regency are 4 (four). First, the coordination of parents to teachers in order to provide numbers. Second, competition competition. Third, informing students of the results, Fourth, giving rewards.